Body composition by impedanciometry of the employees of a high complexity health institution in Tunja (2022)
Introduction: The nutritional status of the general population is important because of the implications with metabolic pathologies, so tools or methods should be used to evaluate it accurately to guide an adequate individual treatment. Objective: To determine body composition by means of impedanciometry in health personnel in a high complexity institution in the city of Tunja, Boyacá. Methodology: An observational, descriptive and cross-sectional study was carried out in which employees of the Hospital Universitario San Rafael de Tunja were included, where all of them were summoned for voluntary participation, an informed consent was applied, and then anthropometric measurements were taken. All the data were collected by the researchers in the Excel program version 2013 and analyzed in the statistical program SPSS version 22. Results: A total of 114 employees of the institution participated in the study. The 74.56% were women, the average age of the general population was 38.39 (SD 11.68 years). Of the total participants, 48.24% had normal nutritional status, 42.10% in overweight, 8.77% in grade I obesity and 0.87% in grade II obesity. Conclusions: The percentage of people with elevated body mass indexes is more than 50%, which should be allowed or generate the implementation of prevention and control strategies to avoid the appearance of chronic secondary diseases and their repercussions.